2023
DOI: 10.3389/fneur.2023.1136408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-acute COVID-19 syndrome on the functional brain networks of non-hospitalized individuals

Abstract: IntroductionThe long-term impact of COVID-19 on brain function remains poorly understood, despite growing concern surrounding post-acute COVID-19 syndrome (PACS). The goal of this cross-sectional, observational study was to determine whether there are significant alterations in resting brain function among non-hospitalized individuals with PACS, compared to symptomatic individuals with non-COVID infection.MethodsData were collected for 51 individuals who tested positive for COVID-19 (mean age 41±12 yrs., 34 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In terms of the psychological burden, results are also consistent with the similar levels of symptom burden seen in this study's COVID‐19 and control groups as examined in Churchill et al. ( 2023 ). However, these findings may be due to the relatively mild sequelae in the current sample of non‐hospitalized individuals with COVID‐19, compared to others who may experience flagrant PACS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of the psychological burden, results are also consistent with the similar levels of symptom burden seen in this study's COVID‐19 and control groups as examined in Churchill et al. ( 2023 ). However, these findings may be due to the relatively mild sequelae in the current sample of non‐hospitalized individuals with COVID‐19, compared to others who may experience flagrant PACS.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that, contrary to study hypotheses, PACS alone does not substantially alter functional brain dynamics relative to symptomatic non-COVID infection, despite evidence of COVID-19 targeting brain tissues (Baig et al, 2020;Galea et al, 2022). In terms of the psychological burden, results are also consistent with the similar levels of symptom burden seen in this study's COVID-19 and control groups as examined in Churchill et al (2023). However, these findings may be due to the relatively mild sequelae in the current sample of non-hospitalized individuals with COVID-19, compared to others who may experience flagrant PACS.…”
Section: Discussionsupporting
confidence: 64%
“…Other associated factors (e.g., post-traumatic stress disorder, medical comorbidities, reinfections, and increasing age) may also be related to the development of "delayed" post-COVID cognitive symptoms. Post-COVID cognitive symptoms may arise from a combination of biological factors, e.g., persistent viral damage, neuroinflammation, damage to the blood-brain barrier, neural network dysfunction, or altered excitability and neurotransmission in the primary motor cortex (Ortelli et al, 2002;Burks et al, 2021;Churchill et al, 2023), as well as psychological factors, e.g., anxiety, depression, or posttraumatic stress disorder (PTSD) . Considering the long regeneration time of nervous system neurons, the recovery of post-COVID cognitive symptoms could be longer than expected.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that one patient who had sensorineural hearing loss of the left ear as a consequence of COVID-19 showed hypometabolism of the left temporal region on 18 F-FDG PET/CT scans and anomalies in rsf-MRI in the same region (29). Another study using rsf-MRI, led by Churchill et al (30), demonstrated that patients who are currently experiencing a larger number of Neuro-PASC symptoms tended to have altered connectivity between parietal, temporal, occipital and subcortical regions using BOLD rsf-MRI. Additionally, distinct patterns correlated to the intensity of PASC symptoms.…”
Section: Functional Mrimentioning
confidence: 99%
“…Additionally, distinct patterns correlated to the intensity of PASC symptoms. They elude to the fact that this could be a useful tool to differentiate between Neuro-PASC and other non-COVID-related infections (30).…”
Section: Functional Mrimentioning
confidence: 99%